Development Of Augmented Reality Arabic For Islamic Tourism: Sustainable Education Need Analysis - Mohammad Najib Jaffar; Azman Ab Rahman; Kirembwe Rashid Abdul Hamed; Mohammad Imran Ahmad; Mahyudin Ritonga; Muhammad Harith Noor Azam (Department of Arabic Language Education, Universitas Islam Negeri Maulana Malik Ibrahim Malang, Indonesia, 2024)
Indexed by WOS